1995
DOI: 10.1073/pnas.92.12.5451
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the cell-cycle inhibitor Cip1/WAF1 and the E1A-associated p300 protein in terminal differentiation.

Abstract: The mechanism of cell cycle withdrawal during terminal differentiation is poorly understood. We report here that the cyclin-dependent kinase (CDK) inhibitor p21ciPl/wAFl is induced at early times ofboth keratinocyte and myoblast differentiation. p2jCiPl/WAF1 induction is accompanied by a drastic inhibition of total Cdk2, as well as p21CiPl/wAFl-associated CDK kinase activities. p21ciPl/wAFl has been implicated in p53-mediated G, arrest and apoptosis.In keratinocyte differentiation, Cipi/WAFi induction is obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
272
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 315 publications
(294 citation statements)
references
References 26 publications
20
272
2
Order By: Relevance
“…In examining the process of cell-cycle withdrawal accompanying differentiation, p21 levels have been shown to increase during NGF treatment of neuroblastoma (Poluha et al, 1996) and PC12 cells (Yan and Zi , 1995;van Grunsven et al, 1996a). This correlation is not limited to neural cells, as induction of p21 mRNA and protein has been detected during myogenic (Guo et al, 1995;Halevy et al, 1995), keratinocytic (Missero et al, 1995), promyelocytic (HL-60) (Jiang et al, 1994;Steinman et al, 1994), and human melanoma cell di erentiation (Jiang et al, 1995).…”
Section: Discussionmentioning
confidence: 98%
“…In examining the process of cell-cycle withdrawal accompanying differentiation, p21 levels have been shown to increase during NGF treatment of neuroblastoma (Poluha et al, 1996) and PC12 cells (Yan and Zi , 1995;van Grunsven et al, 1996a). This correlation is not limited to neural cells, as induction of p21 mRNA and protein has been detected during myogenic (Guo et al, 1995;Halevy et al, 1995), keratinocytic (Missero et al, 1995), promyelocytic (HL-60) (Jiang et al, 1994;Steinman et al, 1994), and human melanoma cell di erentiation (Jiang et al, 1995).…”
Section: Discussionmentioning
confidence: 98%
“…Binding of p300/CBP by E1A inhibits the transcription of the p21 CIP1/WAF1 induced by DNA damage (Steegenga et al, 1996;Somasundaram and el-Deiry, 1997), transforming growth factor-b (TGF-b) (Datto et al, 1997), keratinocytes and myoblasts terminal differentiation (Missero et al, 1995;Cenciarelli et al, 1999). In the cases above mentioned, the transcription of p21 CIP1/WAF1 depends either on p53 (Vogelstein et al, 2000) or on differentiation-specific factors like MyoD (Cenciarelli et al, 1999), RB family proteins and small DNA virus oncoproteins A Felsani et al and p300/CBP is the transcriptional coactivator both of p53 (Avantaggiati et al, 1997;Lill et al, 1997) and MyoD (Eckner et al, 1996;Yuan et al, 1996).…”
Section: Adenovirus Early-region 1amentioning
confidence: 99%
“…Deletion of p21 was not able to substitute for p53 de®ciency in the rescue of the MDM2 null embryonic lethality, described above (Montes de Oca Luna et al, 1997). Moreover, although the p21 CIP1 gene is transcriptionally activated by p53 (el-Deiry et al, 1993), p21 CIP1 is also upregulated during myogenic di erentiation by a p53-independent mechanism thought to involve MyoDmediated transactivation (Parker et al, 1995;Guo et al, 1995;Halevy et al, 1995;Missero et al, 1995). It has also been shown that p21 CIP1 is poorly expressed in RMS cells lines, concomitant with both MyoD and p53 inactivity, and failure to G 1 arrest (Otten et al, 1997).…”
Section: Digging Deeper ± Prb and P53 At The Crossroadsmentioning
confidence: 99%